2015
DOI: 10.1517/14656566.2015.1052742
|View full text |Cite
|
Sign up to set email alerts
|

Use of nitrates in ischemic heart disease

Abstract: Short-acting nitrates are beneficial in acute myocardial ischemia. However, many unresolved questions remain about the use of long-acting nitrates in stable ischemic heart disease. The use of long-acting nitrates is weakened by the development of endothelial dysfunction and tolerance. Also, we currently ignore whether lower doses of transdermal nitroglycerin would be better than those presently used. Multivariate analysis data from large nonrandomized studies suggested that long-acting nitrates increase the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…2 ) [ 61 ]. While this data from GRACE confirms similar findings of an earlier study, [ 62 ] whether this link is causal remains to be determined [ 63 ].
Fig.
…”
Section: Nitratessupporting
confidence: 89%
“…2 ) [ 61 ]. While this data from GRACE confirms similar findings of an earlier study, [ 62 ] whether this link is causal remains to be determined [ 63 ].
Fig.
…”
Section: Nitratessupporting
confidence: 89%
“…Recently, the safety of long acting nitrates has been questioned. Long-term use of nitrates has been linked to induction of oxidative stress, increase in sympathetic activation leading to endothelial dysfunction [67]. A study from Japan including 1429 patients with vasospastic angina showed increased risk of adverse cardiovascular events when long acting nitrates were added to CA therapy [68].…”
Section: Management Of Anginamentioning
confidence: 99%
“…Other uses for nitrates include preeclampsia and pulmonary hypertension 8,16 . Nitrates can be divided into long acting agents such as isosorbide mononitrate (ISMN), and short acting agents such as glyceryl trinitrate (GTN) 9 . Routes of administration of the nitrates are sublingual, oral, injectable and transdermal 14 .…”
Section: Introductionmentioning
confidence: 99%
“…These side effects have a major impact on the patient's tolerability and might negatively affects his / her compliance 3 . Additionally, nitrate tolerance is one of the major issues reported with the continued use of nitrates and could be prevented by allowing a daily nitrate-free interval 9,12,18 . These effects make patients' education an important step in the treatment process since the patient tolerability to the adverse effects and reduction of the drugs' tolerance would improve efficacy of the drugs in controlling the disease and consequently the patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%